2014
DOI: 10.1242/jeb.112391
|View full text |Cite
|
Sign up to set email alerts
|

Encoding wide-field motion and direction in the central complex of the cockroach, Blaberous discoidalis

Abstract: In the arthropod brain, the central complex (CX) receives various forms of sensory signals and is associated with motor functions, but its precise role in behavior is controversial. The optomotor response is a highly conserved turning behavior directed by visual motion. In tethered cockroaches, 20% procaine injected into the CX reversibly blocked this behavior. We then used multichannel extracellular recording to sample unit activity in the CX in response to wide-field visual motion stimuli, moving either hori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 43 publications
(48 reference statements)
3
43
1
Order By: Relevance
“…This function for the CX has been described in locusts and butterflies (Danaus plexippus) but may be common across insect orders (79). Further, in S. gregaria (80), the cockroach Blaberus discoidalis (75), and Drosophila melanogaster (81,82), the CX encodes topographically organized visual information on moving objects and is capable of factoring out the confounding effects of visual motion generated by self-movement from moving objects in the environment (82). In Drosophila, neural activity within the CX encodes the fly's heading relative to visual landmarks in the environment and presumably enables the fly to maintain a course relative to those landmarks (83).…”
Section: Consciousness In Insectsmentioning
confidence: 86%
See 2 more Smart Citations
“…This function for the CX has been described in locusts and butterflies (Danaus plexippus) but may be common across insect orders (79). Further, in S. gregaria (80), the cockroach Blaberus discoidalis (75), and Drosophila melanogaster (81,82), the CX encodes topographically organized visual information on moving objects and is capable of factoring out the confounding effects of visual motion generated by self-movement from moving objects in the environment (82). In Drosophila, neural activity within the CX encodes the fly's heading relative to visual landmarks in the environment and presumably enables the fly to maintain a course relative to those landmarks (83).…”
Section: Consciousness In Insectsmentioning
confidence: 86%
“…The effect of Ampulex venom on the cockroach brain is thus to eliminate the capacity of the roach to organize and initiate behavior (73). This example shows that the central brain structures are key for the initiation and direction of movement in cockroaches and crickets (74,75).…”
Section: Consciousness In Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…While most CX units show an increase in their firing rate preceding the initiation of locomotion, some show a decrease indicating that the CX is predominantly permissive in walking (Guo and Ritzmann, 2013). In a recently published study, injection of procaine into the CX of Blaberus discoidalis was performed, to investigate its role in optomotor behavior (Kathman et al, 2014); the authors found deficits in optomotor behavior after procaine injection but no significant change in general activity (i.e. walking).…”
Section: Discussionmentioning
confidence: 99%
“…First, to determine the role that the CX plays in the control of spontaneous walking, we focally injected procaine to the CX to reversibly decrease neuronal activity specifically in this region (Devaud et al, 2007;Gal and Libersat, 2010;Kathman et al, 2014). Compared with the baseline walking duration, cockroaches that were injected with procaine to the CX walked significantly less, if at all, for 30 min after the injections (P<0.05; Fig.…”
Section: A Procaine Injection To the CX Decreases Spontaneous Walkingmentioning
confidence: 99%